Comparison of Field Measurements with Simulations of Transients in an Arc Furnace - Bianchi Lastra, Raúl E. (1997)
Coordination studies on the protection systems of an arc furnace were required. The protection scheme consists of ZnO surge arresters and RC suppressors. Field measurements on switching transients were performed in order to get information for building and validation of an ATP model of the system. The model was build for simulating switching operations that are not easy to be tested in the real system or difficult to record, such as multiple re-ignitions of the arc in the circuit breaker. MODELS was used to build the control logic that simulates the multiple re-ignitions of the arc. In this paper are presented the results of the simulations with the digital model, and their comparisons with the transients recorded during field measurements. Transients of opening (with and without load), and closing of the circuit breaker were recorded and simulated.